Effect of liner characteristics on teat apex condition and milk flow traits - Alberto Tamburini; Chiara Penati; Luciana Bava; Maddalena Zucali (Italian Journal of Animal Science, 2010)
Milking machine characteristics, as liner type, can influence milk flow trait and teat apex condition. The aim of the study was to investigate the effects of liner type on milk flow traits and teat apex condition. In addition, the age of the liner was taken into account. Four commercial farms were visited three times in order to monitor milk flow traits and teat apex condition. Electronic milk flow meters were used. Teat apex condition was assessed following Teat Club International guidelines. Results of the multiple correspondence analysis showed that the farms with triangular liner, percentage of teats rough and very rough less than 20% of the total teats and overmilking less than 0.5min were clustered in the same space and showed a positive correlation. In contrast, they had a negative correlation with farms having higher percentages of teats with hyperkeratosis, longer overmilking phase and with farms using round liners.